Satisfaction among people living with HIV/AIDS accessing ART services: a hospital-based study - Sharma, Ruchika; Bijlwan, Aanchal; Mishra, Vartika; Bhatnagar, Dinesh (International Journal Of Community Medicine And Public Health, 2025)
Background: HIV/AIDS is a sexually transmitted with possibly no cure, it is a persistent epidemic and a major global public health issue. Through ART centres, which are often developed in hospital settings, the public sector provides care and treatment services for PLHIV. An important tool for getting feedback from the PLHIV is a satisfaction survey. Hence present study was conducted in an ART centre facility to explore satisfaction regarding ART services among PLHIV. Methods: Present study was a cross-sectional study done to assess the satisfaction levels among people living with HIV/AIDS accessing ART services at a hospital-based ART centre at tertiary care teaching hospital. After obtaining socio demographic details, study subjects were subjected to standard PSQ-18 questionnaire for determining satisfaction. Results: With regard to health care services, participants in general have been found to be satisfied with the services and quantification of this is depicted by 74% overall satisfaction reported by study participants. Mean satisfaction was found to be highest in technical quality (4.073±0.436) followed by general satisfaction (4.004±0.422) and lowest scores were found for financial aspects (3.201±0.702) and accessibility/convenience (3.157±0.441). Conclusions: In order to increase PLHIVs’ satisfaction with care, policymakers, programme managers, and service providers may find it useful to prioritise and deliver specific care facets.